Expressão de ISG15 em leucócitos de ovelhas suplementadas com progesterona no anestro estacional - Manta, Manuela Wolker (2020)
The aim of this study was to evaluate the effect of supplementation with exogenous progesterone on the expression of ISG15 in leukocytes and concentration of serum progesterone, on days 10 and 16 of early pregnancy in ewes. The ewes were randomly allocated into two groups: Control Group (GC) and Group P4 (P4G), during seasonal anestrous period and breeding season. The groups were submitted to estrous cycle manipulation protocol. In both periods, P4G received a dose of injectable progesterone on day 3 after mating (25 mg), while the CG received the same vehicle volume. During the non-breeding season, the expression of ISG15 in leukocytes at day 10 did not differ between the groups, P4G and GC (p> 0.05). On the other hand, the expression of ISG15 on day 16 is higher in the CG, when compared to the P4G (p <0.05). During breeding season, the results of ISG15 gene expression did not show differences between groups on days 10 and 16. During non-breeding season, on day 10, the P4G showed lower concentrations of serum progesterone when compared to the CG. On day 16, serum progesterone concentration also decreased in P4G compared to CG. During the breeding season, serum progesterone at D10 did not differ between the groups, P4G and GC (p> 0.05). On the contrary, P4G showed higher concentrations of circulating progesterone when compared to GC on day 16. The results indicate that progesterone supplementation at the beginning of pregnancy in sheep in the seasonal anestrus is not effective in increasing endocrine signaling in maternal recognition of pregnancy or raising serum progesterone, however, it increases serum progesterone during the reproductive season without changing the relative expression of ISG15 in leukocytes.